2005
DOI: 10.1021/ja053945v
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Biosynthesis of Plant Polyketides:  Chain Length Control in an Octaketide-Producing Plant Type III Polyketide Synthase

Abstract: The chalcone synthase (CHS) superfamily of type III polyketide synthases (PKSs) produces a variety of plant secondary metabolites with remarkable structural diversity and biological activities (e.g., chalcones, stilbenes, benzophenones, acrydones, phloroglucinols, resorcinols, pyrones, and chromones). Here we describe an octaketide-producing novel plant-specific type III PKS from aloe (Aloe arborescens) sharing 50-60% amino acid sequence identity with other plant CHS-superfamily enzymes. A recombinant enzyme e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
190
1
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(202 citation statements)
references
References 22 publications
9
190
1
2
Order By: Relevance
“…A recent work revealed that incubation of the recombinant wildtype OKS and malonyl-CoA yielded SEK4 and SEK4b through sequential condensation of eight molecules of malonyl-CoA ( Fig. 2A) (13). These two compounds have been reported to be the spontaneously cyclized products of the nascent octaketide chain synthesized by some type II minimal PKSs such as the actinorhodin minimal PKS (14).…”
Section: Plant Type III Pkssmentioning
confidence: 95%
See 1 more Smart Citation
“…A recent work revealed that incubation of the recombinant wildtype OKS and malonyl-CoA yielded SEK4 and SEK4b through sequential condensation of eight molecules of malonyl-CoA ( Fig. 2A) (13). These two compounds have been reported to be the spontaneously cyclized products of the nascent octaketide chain synthesized by some type II minimal PKSs such as the actinorhodin minimal PKS (14).…”
Section: Plant Type III Pkssmentioning
confidence: 95%
“…An OKS mutant in which Gly 207 was substituted with bulky Met as in PCS completely lost the octaketide-forming activity. However, the mutant PKS efficiently produced an unnatural pentaketide, 2,7-dihydroxy-5-methylchromone that is a regioisomer of 5,7-dihydroxy-2-methylchromone produced by PCS (13). Similarly, the PCS M207G mutant produced the octaketides SEK4/SEK4b instead of the pentaketide chromone (16).…”
Section: Plant Type III Pkssmentioning
confidence: 99%
“…The best-studied type III PKS is CHS, which carries out the first committed step in flavonoid biosynthesis by catalyzing the sequential decarboxylative addition of three acetate units from malonyl-CoA to a p-coumaryl-CoA starter molecule derived from the general phenylpropanoid pathway. Moreover, other members of the type III PKS superfamily in plants use linear acyl-CoAs of varying length (C2 to C20) as starter substrates and give rise to a large variety of metabolites (Austin and Noel, 2003;Abe et al, 2004Abe et al, , 2005Mizuuchi et al, 2008;Flores-Sanchez and Verpoorte, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the regular CHS did not accept the bulky substrate. Further, octaketide synthase (OKS) from Aloe arborescens (12), which normally catalyzes iterative condensations of eight molecules of malonyl-CoA to produce the aromatic octaketides SEK4 and SEK4b, only afforded a tetraketide pyrone as a minor product by condensation of 2-carbamoylbenzoyl-CoA with three molecules of malonyl-CoA (Fig. S3).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, type III PKSs exhibit remarkable substrate tolerance, accepting a series of nonphysiological substrate analogues to produce chemically and structurally distinct unnatural novel polyketides (4)(5)(6)(7)(8)(9)(10). Furthermore, recent structure-based engineering of functionally divergent type III PKSs has significantly expanded the catalytic repertoire of the enzymes and the product diversity (11)(12)(13)(14)(15)(16)(17). Due to their remarkable substrate promiscuity and catalytic potential, the structurally and mechanistically simple type III PKS enzymes represent an excellent platform for the further development of unnatural novel biocatalysts with unprecedented catalytic functions (18).…”
mentioning
confidence: 99%